In vivo comparative study of hydroxyapatite labeled with different radioisotopes: evaluation of the scintigraphic images - Couto, R. M.; De barboza, M. F.; De souza, A. A.; Muramoto, E.; Mengatti, J.; De araújo, E. B. (Cellular and Molecular Biology, 2010)
Radyosinovectomy (RSV) is a radiotherapeutic modality where a Î²-emitting radionuclide is administered locally by intra-articular injection on the form of a colloid or radiolabeled particulate. RSV is a well-accepted therapeutic procedure in inflammatory joint diseases and has been successfully employed for more than 50 years as a viable alternative to surgical and chemical synovectomy. The aim of this work is to compare the in vivo stability of hydroxyapatite labelled with 177Lu, 90Y and 153Sm. All radionuclides were labelled with high yield and were retained in the joint for 7 days, showing stability and usefulness as tools in the RSV treatment. A similar retention of the products in the muscle was observed when the particles were administrated in the muscle. However, the pure form of the radionuclides were rapidly cleared from the blood and accumulated in the liver when injected i.v.. Although 153Sm-HA is already available for nuclear medicine procedures and clinical studies with 90Y-HA have been developed, 177Lu-labeled RSV agents will be economically more viable and has not been studied yet. Its favorable characteristics contribute to follow, to predict and asses the success of RSV by bone scintigraphy studies.